Cold sintering-assisted low temperature fabrication of dense Ba5Nb4O15 ceramics - Sukkha, Usa; Teandam, Apichayaporn; Pakawanit, Phakkhananan; Kamonpha, Phitsamai; Vittayakorn, Wanwilai; Pulphol, Phieraya; Vittayakorn, Naratip (My University, 2026)
This study presents a novel approach for fabricating Ba5Nb4O15 (BNO) ceramics at low sintering temperatures via the cold sintering process (CSP), using Ba(OH)2·8H2O (BOH) as a transient liquid phase. CSP was performed under an external pressure of 10MPa with a sintering temperature range of 150°C to 300°C. Optimally, BNO-BOH ceramics achieved a relative density of 93.7 ± 0.43 when sintered at 250°C for 1h. Scanning electron microscopy (SEM) suggested that particle densification occurred via a dissolution-precipitation process, which filled pores and formed necks between particles. The study demonstrates that the residual liquid content is crucial for ceramic densification. Annealing the as-cold sintered BNO-BOH ceramics at 1000°C for 1h successfully eliminates the BaCO3 secondary phase. Furthermore, dielectric properties of annealed ceramics were also characterized at room temperature from frequency range of 20Hz to 2MHz. The dielectric permittivity is reported to be 39.2 and 0.01 for tanδ at 1.8MHz. The cold sintering process provides an effective strategy to reduce the sintering temperature while achieving high relative density. This method offers a promising alternative for the fabrication of advanced ceramics.
Keywords: Ba5Nb4O15 ceramic; Cold sintering process; Low-temperature densification; Transient liquid phase